EFFECT OF COEFFICIENT OF DEMAND ELASTICITY ON PRICES OF AGRICULTURAL AND ALIMENTARY PRODUCTS - Momirović, Dragan (Economics of Agriculture, 2007)
Therefore empiric research of demand elasticity of agricultural and alimentary products of Slovenia from year 2001 have been used, considering therefore that we could approximately explain how relative changes in prices and income effect demand of these products and how tendencies and trends which are specific for Market of agricultural and alimentary products in this country, would sooner or later reflect in our market too.The results that appeared, show that coefficient of price elasticity on demand for group of agricultural-alimentary products (flour, milk and dairy products, fat and oil, vegetables, fruits etc) have relative low value, less than zero, so each price increase evokes relative low decrease of demand which indicates the conclusion that demand is inelastic and such products belong to so called necessity – subsistence products.Apart from that, cross-elasticity of demand are very low so any price changes upwards and downwards are negligible to changes on demand. Coefficient of income elasticity of demand for group of agricultural products, whose value is less that zero (flour products, vegetables, oil and fat, confectionery products, soda drinks and others) belong to so called necessity products and each income fluctuation would not substantially affects increase of demand, because previous income level has attained certain saturation point. Coefficients of demant elasticity have notable analitical significance for management in business policy of company, especially price policy and planning of agricultural production.